Crystalline anisotropy effect on magnetic properties and its competition with shape anisotropy - Lee, Tae Hwan; Koo, Hyun Cheol; Kim, Hyung-jun; Han, Suk Hee; Lim, Sang Ho (Metals and materials international, 2011)
Shape and crystalline anisotropies compete when their easy axes are perpendicular. The critical aspect ratio, which is the aspect ratio required to offset the crystalline anisotropy, was observed in an effort to investigate the quantitative contribution of crystalline anisotropy using micromagnetic simulation. For a 0.25 μm width hcp -Co pattern, an aspect ratio of 2.7 is required in order to cancel out a crystalline anisotropy constant of 26 kJ/m 3 . The magnetic switching properties are also affected by crystalline anisotropy, which causes the magnetic domain to be narrowed during the reversal process.